Impact of an educational program including a fortiﬁed bread to reduce levels of anemia in school children of Yocará (Puno, Peru) - Soncco-Sucapuca, Maritza (2018)
Apply the educational program Happy Children Without Anemia (HCWA) in children at a public school in Puno department, supplying a fortified vegetable product to reduce anemia levels and improve their parents´ knowledge and healthy practices. A pre-experimental study with pre and post-test was carried out. The study population was children of the public school of Yocará, community of the province of San Roman. Hemoglobin data was obtained from 44 school-age children, ranging from 6 to 12 years old, who received bread fortified with beans and quinoa flour for 120 days. In the same way, both parents and students participated in nutritional talks and workshops with topics related to iron deficiency. The mean hemoglobin level was significantly increased to 0.51 g / dl (p <0.05), it was also possible to reduce mild anemia from 25.5% to 2.3% and moderate anemia from 18.6% to 7%. As for the knowledge of the parents, these increased from an average of 1.96 to 9.38 points according to pre and post test data respectively, evidencing a t = -10,195 (p <0.05). The educational program HCWA, which included the supply of bread enriched with quinoa flour and beans, reduced the anemia of 44 children.